Vocal correlates of individual sooty mangabey travel speed and direction - Christof Neumann; Klaus Zuberbühler (PeerJ, 2016)
Many group-living animals coordinate movements with acoustic signals, but so far most studies have focused on how group movements are initiated. In this study, we investigated movement patterns of wild sooty mangabeys (Cercocebus atys), a mostly terrestrial, forest-dwelling primate. We provide quantitative results showing that vocalization rates of mangabey subgroups, but not of focal individuals, correlated with focal individuals’ current movement patterns. More interestingly, vocal behaviour predicted whether individuals changed future speed, and possibly future travel direction. The role of vocalizations as a potential mechanism for the regulation of group movement was further highlighted by interaction effects that include subgroup size and the quality of poly-specific associations. Collectively, our results suggest that primate vocal behaviour can function beyond travel initiation in coordination and regulation of group movements.